Initial conditions for preparation of thin AlN films by atomic layer deposition. (April 2020) - Beshkova, M; Blagoev, B S; Mehandzhiev, V; Yakimova, R; Georgieva, B; Avramova, I; Terziyska, P; Kovacheva, D; Strijkova, V
Abstract: Thin AlN films were grown on Si substrates in a Beneq TFS-200 ALD reactor. The atomic layer deposition (ALD) process consisted of two half cycles – aluminum adsorption and nitridization separated by a purging step. TMA (trimethylaluminum) and NH3 were used as precursors, and nitrogen (N2 ), as a carrier gas. The pulse duration, purging time, deposition temperature and other deposition conditions were varied to obtain AlN films with desired properties. The X-ray diffraction (XRD) data showed that the AlN films had an amorphous character. The films' chemical composition and bonding states were investigated by X-ray photoelectron spectroscopy. The high resolution Al 2p and N 1s spectra confirmed the presence of AlN with peaks located at 74.1 eV and 397.7 eV, respectively, for all layers.